The reference apparatus in the bible of Matthew the tenth (1502–1507) - Korogodina, Maria (Knygotyra, 2023)
In the second half of the 15th century, a reference apparatus began to be actively developed in Cyrillic manuscripts. This apparatus included prefaces and tables of contents to parts of books, as well as headers, footers, and marginal instructions containing the numbers and titles of chapters, footnotes, and glosses. It served as an aid for navigating a large volume. At the beginning of the 16th century, Matthew the Tenth compiled a Bible while living in Vilnius and Suprasl Monastery. A scribe not only made extensive use of those elements of the reference apparatus that were included in the manuscripts before him, but also significantly developed the reference system for numbering verses, chapters, and pericopes of the biblical text. Numbering became one of the main tools in Matthew the Tenth’s reference apparatus, and up to three or four different numberings could be used on one folio. In an effort to differentiate them, Matthew the Tenth made use of different colors of ink and unusual numbering systems, including both numerals from non-Cyrillic alphabets (Greek and Glagolitic) and numeral systems of his own invention. An additional tool in the reference apparatus of Matthew the Tenth was the system of footnotes which are placed in the margins and use special signs. For this, the scribe used his own system of footnotes which was designed on the basis of musical notation signs.The Bible of Matthew the Tenth, the predecessor to the biblical editions of Francysk Skaryna, shows how quickly and in what an unusual manner the reference apparatus was developed in the late 15th – first half of the 16th century.
Keywords: Reference Apparatus; Bible; Matthew the Tenth; Cyrillic; Greek and Glagolitic Alphabets